2018
DOI: 10.1007/s00439-018-1893-0
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging epigenomics and contactomics data to investigate SNP pairs in GWAS

Abstract: Although Genome Wide Association Studies (GWAS) have led to many valuable insights into the genetic bases of common diseases over the past decade, the issue of missing heritability has surfaced, as the discovered main effect genetic variants found to date do not account for much of a trait's predicted genetic component. We present a workflow, integrating epigenomics and topologically associating domain data, aimed at discovering trait-associated SNP pairs from GWAS where neither SNP achieved independent genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In parallel with our study, recent research integrated epigenomics and TAD data and discovered T2DM-associated enhancer-promoter SNP pairs from imputed data where neither SNP achieved independent genome-wide significance [42]. Manduchi et al [42] reported that one enhancer-promoter SNP pair, rs7991210-rs3742250, was significantly associated with T2DM in pancreatic islets after main effect filtering (combined P=2.16×10 −9 ). In our data, we attempted to validate this epistasis effect of the SNP pair, rs7991210-rs3742250.…”
Section: Discussionsupporting
confidence: 72%
“…In parallel with our study, recent research integrated epigenomics and TAD data and discovered T2DM-associated enhancer-promoter SNP pairs from imputed data where neither SNP achieved independent genome-wide significance [42]. Manduchi et al [42] reported that one enhancer-promoter SNP pair, rs7991210-rs3742250, was significantly associated with T2DM in pancreatic islets after main effect filtering (combined P=2.16×10 −9 ). In our data, we attempted to validate this epistasis effect of the SNP pair, rs7991210-rs3742250.…”
Section: Discussionsupporting
confidence: 72%
“…Epigenomic information has previously been used to suggest causal variants for autoimmune diseases (Farh et al, 2015) and cancer (Han et al, 2015). Recently, an approach was proposed to identify pairs of potentially interacting variants, in active enhancers and gene promoters, respectively (Manduchi et al, 2018). These approaches make it possible to prioritize genetic markers and genes, but it can be difficult (in the absence of further experiments) to know whether the suggested markers and genes are correct.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to (Manduchi et al, ), we operationally defined active enhancers, promoters, and exons in the relevant heart cellular context as described below, and used the union of these three types of regions as filter. When multiple peak files were available for the same mark, they were first merged.…”
Section: Methodsmentioning
confidence: 99%